1989
DOI: 10.1002/1097-0142(19890615)63:12<2497::aid-cncr2820631223>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Placental proteins in high-grade urothelial neoplasms. An immunohistochemical study of human chorionic gonadotropin, human placental lactogen, and pregnancy-specific beta-1-glycoprotein

Abstract: We examined the presence of human chorionic gonadotropin (HCG) in 16 low-grade and 47 high-grade urothelial neoplasms, including two cases with trophoblastic-like differentiation. In HCG-positive tumors, the presence of human placental lactogen (HPL) and pregnancy-specific beta-1-glycoprotein (SP-1) also was assessed. HCG immunoreactive cells were found in nine of the 47 high-grade tumors (19%), whereas none of the low-grade tumors were positive for HCG. This hormone was predominantly detected in the most undi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 43 publications
1
9
1
Order By: Relevance
“…PSGs are expressed predominantly, but not exclusively in trophoblasts as low levels of expression were detected in a healthy colon and in the squamous epithelium of the esophagus [19,20]. PSG expression has also been reported in tumors of trophoblastic and non-trophoblastic origin [21,22,23]. Similar to the presence of human PSGs in non-placental tissues, mouse PSG18 is expressed in the follicle-associated epithelium of Peyer’s patches potentially playing a role in the interplay between epithelial cells and immune cells in mucosa-associated lymphoid tissue [24].…”
Section: Introductionmentioning
confidence: 99%
“…PSGs are expressed predominantly, but not exclusively in trophoblasts as low levels of expression were detected in a healthy colon and in the squamous epithelium of the esophagus [19,20]. PSG expression has also been reported in tumors of trophoblastic and non-trophoblastic origin [21,22,23]. Similar to the presence of human PSGs in non-placental tissues, mouse PSG18 is expressed in the follicle-associated epithelium of Peyer’s patches potentially playing a role in the interplay between epithelial cells and immune cells in mucosa-associated lymphoid tissue [24].…”
Section: Introductionmentioning
confidence: 99%
“…4, 710 One study found that 9 out of 47 high-grade urothelial neoplasms expressed hCG on immunohistochemistry, and two of these tumors demonstrated trophoblastic-like differentiation. 9 Alternatively, choriocarcinomas may originate from multipotent embryonal cells that became arrested during migration in ectopic locations. However, the majority of such extragonadal germ cell tumors arise from midline structures anywhere between the level of the pineal gland to the coccyx.…”
Section: Discussionmentioning
confidence: 99%
“…In only one of those cases was the neoplasm situated in the renal pelvis and the 54-year-old patient had been treated with nephrectomy. Histological examination of this tumor revealed a transitional cell carcinoma with choriocarcinomatous elements [4]. Grammatico et al described the case of a TCC with choriocarcinomatous differentiation involving the pelvoureteric junction of the kidney in an 84-year-old man with hematuria [2].…”
Section: Discussionmentioning
confidence: 99%